Pustakawan Dan Budaya Perpustakaan - Suwarno, Wiji (STAIN Ponorogo, 2014)
Librarian is not only a man working to serve users, siting behind desk, but he also must be a creative ofcers, who can market him self and his library. This article tries to explore how librarians can infuence his institution with his work culture, and how people could under estimate to them and their institution. Library and librarians must strive to achieve a good governance, and ethics code is a solution to this negative impression to both. Ethics code will guide librarian to act professionally, will increase a brand and an image of them